Sirtuin 2 inhibitor AGK2 exerts antiviral effects by inducing epigenetic suppression of hepatitis B virus covalently closed circular DNA through recruitment of repressive histone lysine methyltransferases and reduction of cccDNA - Kim, Jumi; Ha, Jiseon; Song, Chanho; Sajjad, Muhammad Azhar; Kalsoom, Fadia; Kwon, Hyeonjoong; Park, Jaewoo; Park, Sun; Kim, Kyongmin (Frontiers in Cellular and Infection Microbiology, 2025)
Chronic hepatitis B virus (HBV) infection continues to be a global health concern because current treatments such as interferon-α and nucleos(t)ide analogs cannot fully eliminate the virus due to persistence of covalently closed circular DNA (cccDNA) and integrated HBV DNA. Earlier research suggests that AGK2, a selective SIRT2 inhibitor, suppresses HBV replication by modifying key signaling pathways. This study aimed to further explore the anti-HBV effects of AKG2, particularly its effects on the epigenetic landscape of cccDNA. HBV-transfected and -infected cells were used to assess the impact of AGK2 on viral replication. Changes in SIRT2 expression and α-tubulin acetylation (SDS-PAGE-immunoblotting), core particle formation (native agarose gel electrophoresis and immunoblotting), HBV RNA (northern blotting) and DNA (Southern blotting) synthesis, and cccDNA levels (Southern blotting) were measured. Chromatin immunoprecipitation assays were performed to examine deposition of transcriptionally repressive epigenetic markers on cccDNA. AGK2 reduced expression of SIRT2, increased acetylated α-tubulin levels, and reduced synthesis of HBV RNA and DNA. Importantly, AGK2 also reduced cccDNA levels and increased deposition of repressive histone markers H4K20me1, H3K27me3, and H3K9me3 on cccDNA, mediated by histone lysine methyltransferases such as PR-Set7, EZH2, SETDB1, and SUV39H1. Additionally, there was a reduction in recruitment of RNA polymerase II and acetylated H3 to cccDNA, indicating that AGK2 enhances transcriptional repression. AGK2 suppresses HBV replication through direct antiviral actions, and by epigenetic modulation of cccDNA, indicating that using AGK2 to target SIRT2 and associated epigenetic regulators shows promise as a functional cure for chronic hepatitis B.